'A man who has infinite capacity for making things go': Sir Edmund Taylor Whittaker (1873–1956). Issue 3 (2nd September 2019) - Maidment, Alison; McCartney, Mark
Abstract : Among the leading mathematicians of the nineteenth and twentieth centuries was British mathematician and astronomer, Sir Edmund Taylor Whittaker. Born in Southport, in the north of England, Whittaker began his career at the University of Cambridge, before moving to Dunsink to become Royal Astronomer of Ireland and Andrews Professor of Astronomy at Trinity College, Dublin, and finishing in Scotland as Professor of Mathematics at the University of Edinburgh. Whittaker completed original work in a variety of fields, ranging from pure mathematics to mathematical physics and astronomy, as well as publishing on topics in philosophy, history, and theology. Whittaker is also noted as the first person to have opened a mathematical laboratory—with the focus on numerical analysis—in Great Britain. The purpose of this paper is to give an overview of Whittaker's life, both as an academic and a person.